Allergenic Characterization of Tropomyosin from the Dusky Brown Cockroach, Periplaneta fuliginosa - Jeong, Kyoung Yong (American Society for Microbiology, 2004)
Household arthropods are one of the most common causes of allergic diseases. Four species of cockroaches are found to reside in Korean homes, but published work deals almost exclusively with the German and American cockroaches. This study was undertaken to investigate the cross-reactive allergenic components of the dusky brown cockroach, Periplaneta fuliginosa. Enzyme-linked immunosorbent assay (ELISA) inhibition and immunoblot analyses for the dusky brown cockroach were performed with Blattella germanica and Dermatophagoides farinae allergic sera. cDNA encoding tropomyosin, which is a well known cross-reactive pan-allergen, was cloned by reverse transcriptase PCR, and recombinant protein was produced by using a pET-28b expression system. Native tropomyosin was purified by ammonium sulfate fractionation and electroelution. The immunoglobulin E (IgE) reactivities of native and recombinant tropomyosins were compared by an ELISA inhibition study. All 30 sera tested showed P. fuliginosa-specific IgE, and the IgE-binding reactivity of the P. fuliginosa extract was inhibited as much as 79.4% by a B. germanica extract and as much as 63.3% by a D. farinae extract. The deduced amino acid sequence of cloned cDNA was identical with that of Periplaneta americana tropomyosin (98.5% nucleotide sequence identity). Seven of 26 (26.9%) allergic sera had IgE specific for recombinant protein, and the maximum inhibition of P. fuliginosa-specific IgE achieved with recombinant tropomyosin was 37.7% at an inhibitor concentration of 10 μg/ml. Native tropomyosin inhibited the binding of IgE to the P. fuliginosa, B. germanica, and D. farinae extracts by 65.0, 51.8, and 39% at an inhibitor concentration of 1 μg/ml. P. fuliginosa appears to possess allergens that are highly cross-reactive with allergens of B. germanica and D. farinae. Tropomyosin was found to be a major allergenic component accounting for the cross-reactivity between cockroaches and dust mites.